PEMETAAN STATUS EKONOMI DENGAN MALNUTRISI PADA BALITA BERUSIA 0-59 BULAN - Fariza Nurlianna (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Based on the Health Profile of Sleman Regency in 2018, the distribution of malnutrition prevalence in the working area of ​​the Kalasan Health Center all exceeded the Sleman District Strategic Plan. The prevalence of underweight is highest, the prevalence of stunting is the second highest, and the prevalence of wasting at the fourth highest. Underweight, wasting, and stunting are manifestations of a disturbance in the growth process. The research objective is to examine economic heterogeneity and its correlation with spatial malnutrition and to mapping areas related to malnutrition. The study used a cross sectional design with the determination of a sample of purposive cluster sampling, as many as 615 toddlers. The subjects of the study were all children aged 0-59 months in Selomartani Village. The independent variables are underweight, stunting and wasting. The dependent variable is the economic status. Data analysis using Spearman correlation was continued by mapping using the ArcGIS application. The prevalence of underweight 13.7%, stunting 8.1% and wasting 3.1%. The economic status included in poor families is 7%. The results showed no relationship between economic status and underweight (r = 0.039), no relationship between economic status and stunting (r = 0.012) and no relationship between economic status and wasting (r = 0.025). Malnutrition exists in all strata of economic status both in poor families and in non-poor families.